X-ray diffraction study of structure of CaO-Al2O3-SiO2 ternary compounds in molten and crystalline states - Sokol’skii V.E.; Pruttskov D.V.; Yakovenko O.M.; Kazimirov V.P.; Roik O.S.; Golovataya N.V.; Sokolsky G.V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Anorthite and gehlenite crystalline structure and short-range order of anorthite melt have been studied by X-ray diffraction in the temperature range from room temperature up to ~ 1923 K. The corresponding anorthite and gehlenite phases were identified as well as amorphous component for anorthite samples having identical shape to XRD pattern of the anorthite melt. The structure factor and the radial distribution function of atoms of the anorthite melt were calculated from the X-ray high-temperature experimental data. The partial structural parameters of the short-range order of the melt were reconstructed using Reverse Monte Carlo simulations.